Efektivitas Penggunaan Centrifuge Manual Sederhana Sebagai Alat Peraga Dalam Pembelajaran IPA Terhadap Hasil Belajar Siswa - Pisi Ismarliana; Alfauzan Amin; Wiji Aziiz Hari Mukti (Program Studi Pendidikan Fisika, FKIP Universitas Sriwijaya, 2023)
AbstractThis study aims to find out how the effectiveness of using a simple manual centrifuge as a laboratory tool and teaching aid in science learning affects student learning outcomes at SMPN 14 Bengkulu City. The research method is included in the Quasi Experimental Design in the form of a Nonequivalent Control Group Design. Based on the results of testing the hypothesis of the post-test data for the experimental and control classes using the calculation of the t test using the Independent Sample t test formula, the results are known to have a significance value (0.000 <0.05) so that it can be concluded that Hi is accepted. So the average post-test science learning outcomes of students in the experimental class using a simple manual centrifuge as a visual aid is higher than the average learning outcomes of the control class without using visual aids. So it can be concluded that the use of a simple manual centrifuge as a laboratory tool and as a visual aid in science learning is used effectively for class VII student learning outcomes at SMPN 14 Bengkulu CityKeywords: Teaching Aids, Centrifuge, Science Learning OutcomesAbstrakPenelitian ini bertujuan untuk mengetahui bagaimana efektivitas penggunaan centrifuge manual sederhana sebagai alat laboratorium dan alat peraga dalam pembelajaran IPA terhadap hasil belajar siswa SMPN 14 Kota Bengkulu. Metode penelitian termasuk kedalam Quasi Eksperimental Design dalam bentuk Nonequivalent Control Grup Design. Berdasarkan hasil pengujian hipotesis data post-test terhadap kelas eksperimen dan kontrol menggunakan dengan perhitungan uji t menggunakan rumus Independent Sample t test hasil diketahui nilai signifikansi (0,000 < 0,05) sehingga dapat disimpulkan Hi diterima. Maka rata-rata hasil belajar IPA post-test siswa kelas eksperimen yang menggunakan Centrifuge manual sederhana sebagai alat peraga lebih tinggi dari rata-rata hasil belajar kelas kontrol tanpa menggunakan alat peraga. Sehingga dapat disimpulkan bahwa penggunaan centrifuge manual sederhana sebagai alat laboratorium dan sebagai alat peraga dalam pembelajaran IPA yang digunakan efektif terhadap hasil belajar siswa kelas VII SMPN 14 Kota BengkuluKata kunci : Alat Peraga, Centrifuge, Hasil Belajar IPA